Early cortical processing of pitch height and the role of adaptation and musicality - Andermann, Martin; Günther, Melanie; Patterson, Roy D.; Rupp, André (NeuroImage, 2021)
Pitch is an important perceptual feature; however, it is poorly understood how its cortical correlates are shaped by absolute vs relative fundamental frequency (f0), and by neural adaptation. In this study, we assessed transient and sustained auditory evoked fields (AEFs) at the onset, progression, and offset of short pitch height sequences, taking into account the listener's musicality. We show that neuromagnetic activity reflects absolute f0 at pitch onset and offset, and relative f0 at transitions within pitch sequences; further, sequences with fixed f0 lead to larger response suppression than sequences with variable f0 contour, and to enhanced offset activity. Musical listeners exhibit stronger f0-related AEFs and larger differences between their responses to fixed vs variable sequences, both within sequences and at pitch offset. The results resemble prominent psychoacoustic phenomena in the perception of pitch contours; moreover, they suggest a strong influence of adaptive mechanisms on cortical pitch processing which, in turn, might be modulated by a listener's musical expertise.
Available online 24 October 2020
Gesehen am 16.02.2022